The Effect of Yoga Meditation Practice on Young Adults’ Inhibitory Control: An fNIRS Study - Jiang, Dongdong; Liu, Zongyu; Sun, Guoxiao (Frontiers in Human Neuroscience, 2021)
Objectives: The present study aimed to test the effect of yoga meditation (YoMed) practice on inhibitory control of young adults. Methods: A total of 50 participants (23 male, 21-28 years old) from a university in Jinan, Shandong Province were enrolled in this study. Participants were randomly assigned to a YoMed group or a Control group. Participants’ basic information, physical activity, and inhibitory control were measured. A multi-channel continuous-wave near-infrared spectrometer was used to monitor the brain’s hemodynamic responses. Results: After the intervention, we found significant differences in Flanker tasks between the YoMed group and Control group. The accuracy in the YoMed group was higher than those in the Control group (p < 0.05). Analysis of fNIRS data showed that oxyhemoglobin (oxy-Hb) levels in the prefrontal cortex (PFC) increased in the YoMed group during the Flanker tasks after the YoMed intervention. Conclusion: YoMed has a temporarily promoting effect on the brain activation of young adults. It is an effective and appropriate exercise to improve the inhibitory control of young adults.